Software requirements essentials : core practices for successful business analysis - Wiegers, Karl Eugene, 1953-; Hokanson, Candase (Addison-Wesley, 2023)
Software Requirements Essentials presents 20 core practices for successful requirements planning, elicitation, analysis, specification, validation, and management. Leading requirements experts Karl Wiegers and Candase Hokanson focus on the practices most likely to deliver superior value for both traditional and agile projects, in any application domain. These core practices help teams understand business problems, engage the right participants, articulate better solutions, improve communication, implement the most valuable functionality in the right sequence, and adapt to change and growth. Concise and tightly focused, this book offers just enough pragmatic "how-to" detail for you to apply the core practices with confidence, whether you're a business analyst, requirements engineer, product manager, product owner, or developer. Using it, your entire team can build a shared understanding of key concepts, terminology, techniques, and rationales--and work together more effectively on every project.